Durability of S- and N-doped graphene nanoplatelets for electrode performance in solid-state batteries - Srivastava V.K.; Mourdikoudis S.; Azadmanjiri J.; Kumar P.; Sofer Z. (My University, 2025)
The main emphasis of the present Highlight paper is to summarise reported works aiming to understand the effect of sulfur and nitrogen doping on graphene nanoplatelets for high capacity electrodes in solid-state rechargeable energy storage devices. Lithium-ion batteries are considered to be one of the most promising energy storage devices which have the potential of integrating the high energy granted by lithium-ion batteries and long cycling life of supercapacitors in the same system. However, the present Li-ion batteries provide only high power density due to the low electrical conductivity of the anode materials. Moreover, there is a need to increase the capacity and kinetic imbalances between the anode and cathode by designing high-power and stable structures for the anode and cathode materials. Graphene nanoplatelets (GnPs) have been intensively explored as anode materials in lithium ion batteries due to their unique structure and outstanding electrochemical properties. The synthesis procedure, structure and electrochemical performance of such materials are discussed extensively in this manuscript. © 2024 The Royal Society of Chemistry.